(untitled) (Multidisciplinary Journal of Science and Technology, 2023)
Teaching English as a second language (ESL) or as a foreign language (EFL) is a complex and dynamic endeavor, with a diverse range of teaching methods and approaches. This article explores the key methods and strategies that have proven to be effective in enhancing the teaching and learning of English. The literature review delves into the history of language teaching, highlighting the evolution of methodologies. The methodology section presents practical techniques, tools, and tips for effective language instruction. The results section discusses the outcomes and benefits of these methods, supported by research and real-world experiences. In conclusion, this article emphasizes the importance of a flexible and learner-centered approach to teaching English.